Effect of macronutrient omission on cadmium uptake in rice seedlings - Carrillo Zenteno, Manuel Danilo (2024)
Introduction. The soil and climatic conditions of Ecuador are ideal for rice cultivation, yields are higher than the world average, but agronomic management leads to an increase of cadmium in the soil, which can reach the grain by translocation, which affects its safety. Objetive. To evaluate the absorption of cadmium through the omission of macronutrients technique in six soils of Ecuador and its effect on the vegetative development of rice crops. Materials and methods. The trial was carried out at the Pichilingue Tropical Experimental Station of the National Institute of Agricultural Research, Ecuador, during 2018. Nine treatments were studied: 1) Without fertilization and without Cd (control 1), 2) without fertilization and with Cd (Control 2), 3) Complete fertilization and six omission treatments of one nutrient at a time, a completely randomized block design of experiments, divided plots and three repetitions was used. The variables evaluated were those related to the production of dry matter in the root and aerial part. For the comparison between means, the Tukey test was used (p<0.05). Results.  Nutrients omissions (N and P) led to reduced Cd absorption, which decreased dry matter production, particularly in very acidic or alkaline soils such as in Sucumbíos (pH 4) and Guayas (pH 7, 9), respectively. Conclusions. The absorption of cadmium in rice plants was reduced to a greater extent with the omission of the macronutrients N and P, mainly in the soils of Sucumbíos, Los Ríos, El Oro and Manabí, the nutrient omission technique also affecting the production of dry matter and yields, also observing that a pH below 5 or higher than 7.9 affects the absorption of cadmium in the soils studied.